The Dhikr and Healthy aging in Indonesia: A Literature Review - Sufyan Anwar; Marniati; Enda Silvia Putri; Khairunnas; Itza Mulyani; Jun Musnadi Is; Maiza Duana (Archives of Current Research International, 2023)
Introduction: The increasing elderly population poses a unique challenge to countries, particularly in the field of healthcare. This study aims to identify evidence of the connection between dhikr and health among the elderly in Indonesia. Study Design: A literature review of research articles utilizing quantitative approaches, including observational and experimental studies. Article searches were conducted using data from PubMed, ProQuest, and Google Scholar, with publication limits set from 2013 to June 21, 2023. The research was conducted in Indonesia, and the participants were Indonesian Muslims aged 60 years or older. Results: A total of 25 articles were found through ProQuest, 115 through Google Scholar, and none through PubMed. Sixteen articles met the predetermined criteria, including one observational study and 15 experimental studies. Some researchers in the experimental studies combined dhikr with other interventions, including breathing exercises, ablution, and prayer. The phrases uttered during dhikr varied, including Surah Al-Fatihah, Astaghfirullah, Subhanallah, Alhamdulillah, La Ilaha Illallah, Allah Akbar, Ya Rahman, Ya Rahim, and blessings upon the Prophet. Conclusion: Dhikr has a positive impact on improving the health of the elderly, particularly in enhancing psychological well-being and reducing blood pressure.